Stable Deuterium-Tritium plasmas with improved confinement in the presence of energetic-ion instabilities - Jeronimo Garcia; Yevgen Kazakov; Rui Coelho; Mykola Dreval; Elena de la Luna; Emilia R. Solano; Žiga Štancar; Jacobo Varela; Matteo Baruzzo; Emily Belli; Phillip J. Bonofiglo; Jeff Candy; et al. (Nature Communications, 2024)
Abstract Providing stable and clean energy sources is a necessity for the increasing demands of humanity. Energy produced by Deuterium (D) and Tritium (T) fusion reactions, in particular in tokamaks, is a promising path towards that goal. However, there is little experience with plasmas formed by D-T mixtures, since most of the experiments are currently performed in pure D. After more than 20 years, the Joint European Torus (JET) has carried out new D-T experiments with the aim of exploring some of the unique characteristics expected in future fusion reactors, such as the presence of highly energetic ions in low plasma rotation conditions. A new stable, high confinement and impurity-free D-T regime, with reduction of energy losses with respect to D, has been found. Multiscale physics mechanisms critically determine the thermal confinement. These crucial achievements importantly contribute to the establishment of fusion energy generation as an alternative to fossil fuels.